The birth and establishment of film education in Ukraine (1916–1930) - Myslavskyi, V. (PC TECHNOLOGY CENTER, 2023)
The chapter "Birth and development of film education in Ukraine (1916–1930)" consists of two parts. Part 1 "Private Film Education" covers the period from 1916 to 1919. At this time, dozens of film schools, or as they were called film studios, were opened. However, almost all educational institutions at that time did not existed for a very long time. It was related to military operations and the political situation in the country. If we talk about the level of film education at that time, it was of high quality. As a rule, the opening of film schools pursued one single goal – earning money, since many young men and women at that time were fascinated by cinematography and dreamed to be engaged in this art form. Part 2 of the chapter "State film education" covers the period from 1920 to 1930. This was the period of formation of state administration in the republic and development of the Ukrainian film industry. In the early 1920s, there was an acute shortage of qualified cinematographers in Ukraine. The invited film experts from the RSFSR and Germany were a far cry from Ukrainian culture. But most importantly, these directors and screenwriters were of the old formation and did not meet the requirements of the revolutionary time. To solve the propaganda tasks, set by the Communist Party, young, revolutionary-minded cinematographers were needed. To solve this problem, the All-Ukrainian Photo and Film Administration (VUFKU) took measures to open various film institutions for the training of young film specialists. The author analyzes the stages of establishment and development of film education in Ukraine, from film schools, various film courses, to the opening of the Odesa Film School and Kyiv Film Institute.
Keywords: film history; history of cinema; Ukrainian cinematography; кіноосвіта